Sliding mode switched control for Markovian jumping systems subject to intermittent DoS attacks - Chen, Bei; Niu, Yugang (International journal of robust and nonlinear control, 2022)
This article focuses on the sliding mode control (SMC) of Markovian jumping systems subject to network attacks. The transmission from the sensor to the controller may be attacked via the intermittent denial‐of‐service (DoS) pattern. A key issue is to establish a unified SMC framework under different DoS attack status. To this end, a mode‐detector is first employed to estimate the system mode that is unavailable under DoS attacks. And then, a synchronous/asynchronous switching estimator is constructed to observe the unmeasurable system state, meanwhile, estimate the attacked system output. Based on the above estimator, a synchronous/asynchronous switching sliding mode controller is designed, the corresponding sufficient conditions are derived by introducing a novel Lyapunov function. Finally, the proposed switching SMC strategy is illustrated via the simulation examples.